An iterative rectification procedure analysis for historical timber frames: Application to a cultural heritage Chinese Pavilion. (15th January 2021) - Li, Shengcai; Song, Tuo; Milani, Gabriele; Abruzzese, Donato; Yuan, Jianli
Highlights: New iterative rectification algorithms applied to wooded frames. Application to a built heritage pavilion in China. Application of nodal displacements, reinforcement of nodes and elements. Control of the elastic rebound applying counter-displacements large enough. Control of the damage induced by rectification on nodes and elements. Abstract: The paper deals with the challenging problem of the rectification of leaning 3D historical timber frames. A prestigious case study is analyzed, namely the Feiyun Pavilion, PRC. Detailed onsite investigations on geometry, out-of-verticality, damages, material properties and building details are carried out. A finite element (FE) trial and error numerical procedure of rectification is then proposed in a general framework, basing on a discretization into FEs of the frame in its deformed configuration and on the application of horizontal displacements at the nodes belonging to the external box edges. The procedure is automatized in Ansys commercial code; beams, pillars and braces are modeled with an elasto-plastic orthotropic material, whereas for joints non-linear translational and rotational springs are utilized, with non-linear constitutive relationships deduced from suitable experimentation. The following phases define the core of the rectification algorithm: (i) application of the anti-displacements that equal the experimentally measured out-of-verticality values to produce corrective forces, (ii) strengthening of the joints and elements to improve structural stiffness, e.g. with hooping steel belts and reinforcing plate, (iii) removal of the corrective forces and consequent elastic return of the structure to a new position that still exhibits deviation, (iv) re-application of anti-displacements equal to the residual deviation found in (i)+(iii), (v) repetition of phase (i), (iii) and (iv) until the residual deviation is eliminated. The corrective displacements can be obtained by the superposition of anti-displacements applied in each cycle. The procedure is successfully applied in a single benchmark and -using an approximate but effective way- to the complex leaning structure under consideration which requires huge restoration. The approach shows excellent rectification capabilities in the idealized case, as well as a fairly good performance in the case of the existing structure considered as case study, where different deterioration phenomena are taken into account.